The Cultural and Creative Sector in 5 Arab Mediterranean Countries: Skill-Mismatch and Active Labour Market Policies - Hariri, Nizar; Kassis, Grace (European Scientific Journal, ESJ, 2017)
The cultural and creative sector is a major determinant of the economic development. But Arab countries are still incapable of exploiting all its potentialities, while other developing countries are doing much better. Even though this sector is more and more alluring to Arab youth, especially after the Arab spring, yet a lot of artistic and creative activities are not considered as â€œrealâ€ jobs. Our study provides a conceptual framework for understanding the creative economy in Morocco, Tunisia, Egypt, Palestine and Lebanon. In order to address the main challenges to employability, we analyze the market structure in each country, with a view on the production, consumption and trade of creative goods and services. Finally, we suggest recommendations for active labour market policies aiming at enhancing employability in the cultural and creative sectors of the aforementioned countries.